Root development and activity studies in ashgourd - Roselin Sebastian (Department of Agronomy, College of Horticulture, 1987)
Experiments were conducted at College of Horticulture, Vellanikkara during 1985-86 to study the root development and distribution pattern of rainfed and irrigated ashgourd. In the rainfed crop, there were 16 treatments involving placement of 32p at 16 places being the combinations of four lateral and four vertical distances. In the irrigated crop, there were only 12 treatments being the combinations of four lateral and three vertical distances. In the fertilizer experiment there were four treatments viz. no fertilizers and full dose of fertilizer applied at 0-20, 20-40 and 40-60 cm. These were conducted at 0, 15, 30 and 45 days after germination. Growth and uptake of nutrients were studied one month after application. The field experiments were laid out in randomised block design. The root development was very fast in ashgourd. By 30 days, it reached 150cm in rainfed and 60 cm in irrigated conditions. The excavation studies also revealed that the lateral development of roots were more in rainfed reaching a maximum of 182 cm while it was only 75 cm in irrigated, by 100 days. The depth of penetration was almost same in both cases, the values being 87 cm in rainfed and 90 cm in irrigated crop. The crop can be classified as moderately deep rooted. The crop had a sperse root system with only a few primary roots (14 to 18). The primary roots near surface grew laterally without much penetration whereas others developed without much lateral spread. The 32p distribution studies revealed that 32p content was more in fruits. The relative distribution followed the same pattern of dry matter accumulation with maximum in leaves (31%). The fertilizer experiments revealed that the zone of active absorption of nutrients were upto 20cm by 30 days, 40 cm by 45 days and 60 cm by 60 days.